Premarital Sexual Behaviour Among Urban-rural School Teenagers in Southeast Sulawesi, Indonesia: Comparative Study - Yusran, Sartiah; Astina, Astina; Sabilu, Yusuf; Sety, La Ode Muhammad; Akifah, Akifah; Rezal, Farit (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Premarital sex among teenagers keeps soaring by the day across the globe. Indonesia is faced with high levels of sexual promiscuity among adolescents. This research aimed to examine the differences in premarital sexual curiosity between teenagers in rural and urban settings. The population for the research involved 266 senior high school students drawn from Kendari city and the rural area of Ladongi, Southeast Sulawesi, using the Proportional Stratified Random Sampling technique. The research method used a cross-sectional study with a comparative design using the Mann-Whitney Test. The results revealed differences in premarital sexual behavior (p = 0.026), media information (p = 0,000), school’s roles (p = 0,000), and first age of dating (p = 0.038) between teenagers in rural and urban setting. However, there was no difference in knowledge regarding premarital sexual behavior (p = 0.159) and peer pressure (p = 0.219) between rural and urban teenagers.